2014
DOI: 10.1016/j.jpowsour.2014.05.101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron sputtered gadolinia-doped ceria diffusion barriers for metal-supported solid oxide fuel cells

Abstract: Gadolinia-doped ceria (GDC) thin films are deposited by reactive magnetron sputtering in an industrial-scale setup and implemented as barrier layers between the cathode and electrolyte in metal-based solid oxide fuel cells consisting of a metal support, an electrolyte of ZrO 2 co-doped with Sc 2 O 3 and Y 2 O 3 (ScYSZ) and a Sr-doped lanthanum cobalt oxide cathode. In order to optimize the deposition of GDC to obtain high electrochemical performance of the cells, the influence of film thickness and adatom mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The position of the XRD peaks were also altered with the change in annealing temperature. Careful refinment of four intense peaks (figure 1) revealed that the value of FHWM determined using Gaussion fit were slightly higher than the one referred in the database, indicating freely distributed stress in the film [37]. Moreover, the peaks position were occurred at higher angles (2θ=30.22°, 50.51, and 59.98) for sample annealed at 600°C compared to those synthesized at lower temperature 300 to 500°C.…”
Section: Resultsmentioning
confidence: 90%
“…The position of the XRD peaks were also altered with the change in annealing temperature. Careful refinment of four intense peaks (figure 1) revealed that the value of FHWM determined using Gaussion fit were slightly higher than the one referred in the database, indicating freely distributed stress in the film [37]. Moreover, the peaks position were occurred at higher angles (2θ=30.22°, 50.51, and 59.98) for sample annealed at 600°C compared to those synthesized at lower temperature 300 to 500°C.…”
Section: Resultsmentioning
confidence: 90%
“…Knibbe et al (3) reported that grain boundaries of the dense epitaxial GDC layer facilitate Sr diffusion. Decrease of electrochemical performance because of Sr mobility in metal-supported SOFC with magnetron sputtered protective layer, if layer was thinner than 0.6 µm and LSC cathode was sintered at 800°C, has been demonstrated (4). Positive influence of Sr on the GDC densification, having some effect already at 400°C, has been reported by Suresh et al (5).…”
Section: Introductionmentioning
confidence: 85%
“…Especially in devices made of yttria-stabilized zirconia (YSZ) electrolytes and La1-xSrxCo1-yFeyO3-δ (LSCF) electrodes, the diffusion of Sr can lead to the formation of insulating SrZrO3 [1,2]. Gadolinia doped ceria (GDC) thin films can be used in such devices as a Sr diffusion barrier in order to extend their lifetime [3,4].…”
Section: Introductionmentioning
confidence: 99%